Realistic simulations of gravitational lensing by galaxy clusters: extracting arc parameters from mock DUNE images - Meneghetti, Massimo; Melchior, Peter; Bartelmann, Matthias (Arxiv, 2013)
We present a newly developed code that allows simulations of optical observations of galaxy fields with a variety of instruments. The code incorporates gravitational lensing effects and is targetted at simulating lensing by galaxy clusters. Our goal is to create the tools required for comparing theoretical expectations with observations to obtain a better understanding of how observational noise affects lensing applications such as mass estimates, studies on the internal properties of galaxy clusters and arc statistics. Starting from a set of input parameters, characterizing both the instruments and the observational conditions, the simulator provides a virtual observation of a patch of the sky. It includes several sources of noise such as photon-noise, sky background, seeing, and instrumental noise. Ray-tracing through simulated mass distributions accounts for gravitational lensing. Source morphologies are realistically simulated based on shapelet decompositions of galaxy images retrieved from the GOODS-ACS archive. According to their morphological class, spectral-energy-distributions are assigned to the source galaxies in order to reproduce observations of each galaxy in arbitrary photometric bands. We illustrate our techniques showing virtual observations of a galaxy-cluster core as it would be observed with the space telescope DUNE, which was recently proposed to ESA within its "Cosmic vision" programme. (Abridged)
Gesehen am 25.09.2017